Carbon-supported Pt-Co catalysts prepared by a modifled polyol process as cathodes for PEM fuel cells - Santiago, Elisabete I.; Varanda, Laudemir C.; Villullas, H. Mercedes (Amer Chemical Soc, 2007)
In this work, carbon-supported Pt70Co30 nanoparticles were prepared by a polyol process using a long-chain diol as reducer (hexadecanediol) and oleic acid and oleylamine as stabilizers. Depending on the synthesis conditions, Pt70Co30/C nanocatalysts with very small particle size (1.9 +/- 0.2 nm) and narrow distribution homogeneously dispersed on the carbon support and having a high degree of alloying without the need of thermal treatments were obtained. The as-prepared catalyst presents an excellent performance as proton exchange membrane fuel cells (PEMFC) cathode material. In terms of mass activity (MA), the Pt70Co30/C electrocatalysts produced single fuel cell polarization response superior to that of commercial catalyst. To analyze alloying effects, the result of thermal treatment at low temperatures (200-400 degrees C) was also evaluated and an increase of average crystallite size and a lower degree of alloying, probably associated to cobalt oxidation, were evidenced.